Notorious Nineteen - Evanovich, Janet; King, Lorelei (New York : Random House Audio, 2012)
Tracking down a con man who has disappeared from the hospital after an emergency appendectomy, Stephanie Plum calls on Joe Morelli for help when a second felon goes missing from the same hospital.
Unabridged.
Compact discs.
Read by Lorelei King.
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; Trenton (N.J.) -- Fiction; Mystery fiction; Humorous fiction; Audiobooks